Multi-hazard risk assessment - Tan, Jia Hui. (2012)
The series of disasters following the 11 March 2011 Tohoku earthquake (Mw 9.0) is a clear example of the need of managing risks from multiple sources. These sources can be correlated or independent. For example, the disaster was characterised by the occurrence of subsequent events (i.e. earthquake, tsunami and nuclear risk) as well as independent events (e.g. the heavy snow and harsh weather conditions following the earthquake). The scope of this project is to analyse methods of assessing risks from multiple sources, in particular focussing on earthquake and tsunami-related events. The project will include: